2007
DOI: 10.1080/00032710601017821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-Aspartate Concentration on the Response of the Amperometric L-Glutamate Sensor for the Measurement of L-Glutamate and Aspartate Aminotransferase Activity in Serum

Abstract: L-glutamate oxidase was immobilized in a photo-cross-linkable polymer membrane on a palladium strip electrode for the amperometric measurement of aspartate aminotransferas eactivity. The sample, serum for example, was injected into a buffered L-aspartate and a-ketoglutarate solution. L-aspartate is the essential substrate and can transfer to L-glutamate via the aspartate aminotransferase catalyzing reaction. Aspartate aminotransferase activity can be measured by determining the increasing rate of L-glutamate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…[1] In recent years, sub-micron particles have been used as fillers in composites for improving the performance of the composite materials, such as sub-micron SiO 2 /epoxy, submicron TiO 2 /poly-ether-ether-ketone (PEEK), sub-micron silica particles/epoxy, sub-micron TiO 2 /polyethyleneterephthalate (PET), sub-micron silica fillers/epoxy, sub-micron sized copper/ruthenium-tantalum, and sub-micron silica fillers/dental composite resins. [2][3][4][5][6][7][8] The wear resistance of hybrid epoxy composites filled with submicron particles and nanoparticles (submicron-PTFE and nano-ZnO) was also investigated. [9] Inorganic particles enhance the mechanical properties of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In recent years, sub-micron particles have been used as fillers in composites for improving the performance of the composite materials, such as sub-micron SiO 2 /epoxy, submicron TiO 2 /poly-ether-ether-ketone (PEEK), sub-micron silica particles/epoxy, sub-micron TiO 2 /polyethyleneterephthalate (PET), sub-micron silica fillers/epoxy, sub-micron sized copper/ruthenium-tantalum, and sub-micron silica fillers/dental composite resins. [2][3][4][5][6][7][8] The wear resistance of hybrid epoxy composites filled with submicron particles and nanoparticles (submicron-PTFE and nano-ZnO) was also investigated. [9] Inorganic particles enhance the mechanical properties of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…), 7.0(Basu et al 2006, Chang and Chen 2007, Pauliukaite et al 2006) 7.4 (Claussen et al 2011, Jamal et al, 2010, Ryan et al 1997, Tian, et al 2009, Zhang et al 2006), 8.0 (Backer et al 2013) were also reported for glutamate enzyme electrodes.…”
mentioning
confidence: 69%
“…The best current response obtained at 60 C glutamate measurements were performed at body temperature (37 C) because the response current was stable between 35 and 40 C. Moreover, the repeatability of the calibration curves obtained over 40 C was not satisfactory. Different temperatures such as 37 C (Chang and Chen 2007), 35 C (Basu et al 2006, Batra and Pundir 2013, Rahman et al 2005, 42 C (Gholizadeh et al 2012), 25 C (Maalouf et al 2007, Tang et al 2007, Tian et al 2009) were selected as optimum for glutamate biosensors.…”
Section: Optimization Of Experimental Parametersmentioning
confidence: 99%
“…This system can work in a reagent‐less electrochemical sensor since the substrate can be directly embedded in the sensor, reducing the sample handling steps. In this manner, AST can be detected in <5 min at biologically relevant levels, making this a promising approach (Chang & Chen, 2007; Guo et al., 2008; Hsueh et al., 2012).…”
Section: Tailored Biosensing Strategiesmentioning
confidence: 99%